Propositions about the concept of culture and baroque ethos in the work of Bolívar Echeverría - Ramaglia, Dante (2025)
The original work developed by the thinker Bolívar Echeverría is understood as animated by the intention of configuring a critical theory about capitalist modernity that promotes overcoming alternatives. To do so, some of the fundamental conceptions that he proposes in his theses on the cultural field are reviewed from a Latin American perspective. In the first part of the article, the characterization that Echeverría proposes about the concept of culture is reviewed. This notion is understood from a double condition that occurs between social reproduction, which refers to the material sphere of existence, and the production of meanings as a specific capacity of the human being. From this perspective, he tries a communicational and linguistic approach to culture with its correlations with the anthropological and political. In a second part, reference is made to the notion of baroque ethos proposed by the author as a characteristic of Latin American culture. Through this dysfunctional and negative behavior that resorts to imagination, he understands that a strategy of neutralization of the capitalist contradiction is manifested through which everyday life is endured. Finally, certain allusions are pointed out to the political meaning of the author’s reflections on the alternatives to advance towards a post-capitalist society.